Análisis de la potencialidad turística de la Biblioteca Municipal del cantón Puebloviejo - León Cortéz, Mary Siulee (2023)
Inside the province of Los Ríos, in the canton of San Francisco de Puebloviejo, there is located a historical, cultural and literary jewel considered Cultural Heritage. This place is a Library that has ancient books dating since 1768 to 2008. The main objective of this project is to analyze the tourist potential of the Puebloviejo Canton Library. For this, mixed methodology has been used, with qualitative and quantitative approaches for descriptive exploratory research, the data collection technique was used through observation, survey and interview. For the instruments, an observation sheet, closed questions and a questionnaire were used. Through the instruments used, it has been concluded that the Puebloviejo Library has undeniable tourist potential. However, it is regrettable to note that the place is not being preserved with the due attention and care it deserves.